PENGARUH BUDAYA K-POP TERHADAP PENDIDIKAN KARAKTER ANAK BANGSA - Inayatus Saadah , Ida; Ihsanudin, Ihsanudin; Wahyudin, Dede; Damayanti, Yulia; Caturiasari, Jennyta (JURNAL SINEKTIK, 2025)
Character education is education that aims to instill character values in students so that they have good or noble morals, tolerance, and character. Korean culture, or Hallyu, is a South Korean culture that produces many products such as drama, music, movies, fashion, food, and lifestyle that spread in Indonesia. These products are growing more rapidly due to digital-based technology. This research uses qualitative research with a literature review, which is a series of activities related to how to collect data and obtain information based on books, journals, newspapers, magazines, and others. In this study, the researcher used the influence of K-Pop culture on the character education of the nation's children because the nation's children were fanatical and liked K-Pop excessively, so the researcher raised this phenomenon. With this literature study, researchers have a lot of information about the influence of K-pop culture on the character education of the nation's children.Â